Leisure time activities of children: Inequalities, determinants, and inter-relations - Daniela Rodrigues; Aida Isabel Tavares; Aristides M Machado-Rodrigues; Augusta Gama; Helena Nogueira; Maria-Raquel G Silva; Cristina Padez (Bern Open Publishing, 2024)
More studies should adopt a combined approach to modifiable lifestyle behaviors because of their potential synergistic effects on health. This study aims to • observe how boys and girls allocate their time on different activities, during week and weekend days, • investigate the time inter-relations between different leisure activities, and • analyze how child and familial characteristics are associated with children's time use in multiple activities. In 2016/17, a validated questionnaire collected data from 3-10-year-old Portuguese children (n = 8,472). Parents reported their children's time use in different behaviors: sleep, study, screen media use, indoor and outdoor play, and school commute, as well as children's participation in sports, and socio-economic characteristics of the family. A combination of statistical analysis (e.g., t-tests, pairwise correlations and multiple linear regression) revealed that: • boys reportedly have higher screen time than girls, but they also accumulate more time in outdoor play; • the time spent in different activities was determined by a set of family sociodemographic factors, such as urbanization and parental employment; and • exists some inter-relation between leisure activities with high screen time being significantly associated with less sport participation and less sleep duration. Identifying time spent in multiple activities that differ by sex (and associated determinants) is critical for the development of activity promotion strategies, and may help to inform evidence-based policies designed to increase physical activity and decrease sedentary behavior in young children. Present findings highlight the growing importance of electronic media in children's life and how they can displace other leisure activities.